2021
DOI: 10.21873/cgp.20253
|View full text |Cite
|
Sign up to set email alerts
|

G-Protein-coupled Estrogen Receptor 1 Agonist G-1 Perturbs Sunitinib Resistance-related Phosphoproteomic Signatures in Renal Cell Carcinoma

Abstract: Background: Metastatic renal cell carcinoma (RCC) often develops resistance to first-line targeted therapy such as sunitinib. G-Protein-coupled estrogen receptor 1 (GPER1) agonist G-1 was recently reported to regulate RCC physiology but the role of G-1 in RCC tumorigenesis and sunitinib resistance remains largely unknown. Materials and Methods: Parental and sunitinib-resistant 786-O cells were treated with GPER1 agonist G-1, and quantitative phosphoproteomics was performed. Bioinformatic analyses and validatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Oestrogen has been shown to have a negative effect on osteoclastogenesis 16‐20 and is widely accepted as an autophagic activator 25‐32 . An intriguing viewpoint is that autophagy facilitates osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oestrogen has been shown to have a negative effect on osteoclastogenesis 16‐20 and is widely accepted as an autophagic activator 25‐32 . An intriguing viewpoint is that autophagy facilitates osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Oestrogen has been shown to have a negative effect on osteoclastogenesis [16][17][18][19][20] and is widely accepted as an autophagic activator. [25][26][27][28][29][30][31][32] An intriguing viewpoint is that autophagy facilitates osteoclastogenesis. Thus, there might exist a counteracting mechanism between Streicher and Liang et al 54,55 showed that oestrogen suppressed osteoclastogenesis by reducing the expression of RANKL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, GPER-1 expression correlated with favorable clinical outcome in ovarian cancer (19). Also in renal cell carcinoma, activation of GPER1 with the GPER1 agonist G1 has shown an antitumor activity (20). However, a study of GPER1 in breast carcinoma showed that cells treated with tamoxifen, which is an agonist on GPER1, had significantly greater proliferation compared with the control group (21).…”
Section: Relative Gene Expression Of Gper1 In Hela Cells After Gper1 ...mentioning
confidence: 99%
“…Similar to the AR, there are conflicting findings regarding the role of ER expression in RCC. There are data suggesting that ERβ expression inhibits RCC [ 26 , 27 ], while other studies indicated that higher ERβ expression is associated with a poor prognosis [ 28 , 29 ]. Interestingly, the independent role of ERα in RCC prognosis has not yet been determined [ 29 ].…”
Section: Introductionmentioning
confidence: 99%